The Impact of Board Independence and Gender Diversity on Quality of Integrated Reporting: Indonesian ESG-focused Companies - Butar-Butar, Dea Tiara Monalisa; Itan, Iskandar; Saragih, Anre Giltbelt (Universitas Negeri Malang, 2025)
This study investigates the impact of board independence and gender diversity on the quality of integrated reporting (IR) among ESG-focused firms in Indonesia. Integrated reporting, which combines financial and non-financial information, plays a crucial role in enhancing corporate transparency and accountability, particularly in firms committed to environmental, social, and governance (ESG) principles. Grounded in Agency Theory and Resource Dependence Theory, this study employs a quantitative research design using panel data from publicly listed Indonesian companies that issued integrated or sustainability reports between 2020 and 2023. The results reveal that board independence does not have a significant effect on IR quality, suggesting that structural independence may not be sufficient to influence ESG disclosures. In contrast, board gender diversity has a positive and significant effect on IR quality, highlighting the strategic role of diverse perspectives in enhancing reporting practices. These findings provide important insights for regulators, investors, and firms seeking to strengthen governance mechanisms and improve transparency through integrated reporting.